Evidence versus advocacy, as related to radiofrequency denervation in the treatment of chronic low back pain and the MINT trials. Issue 1 (12th December 2019) - Lanier, William L; Neal, Joseph M
Abstract : In 2017, JAMA: Journal of the American Medical Association published the results of the MINT trials, prospective research involving 681 patients, all of whom received exercise therapy for low back pain. Half of the patients were randomized to additionally receive radiofrequency denervation (RFD) treatment. 88% of patients completed the 3-month follow-up, and 77% completed the 12-month follow-up. In this context, RFD provided no added benefit over the baseline of exercise therapy. In 2018, five authors, all experts in pain medicine, published a 'Daring Discourse' article in the journal Regional Anesthesia and Pain Medicine ( RAPM ), criticizing the findings of the MINT trials. Although 3 of the 5 authors of the RAPM 'Daring Discourse' article reported in conflict of interest statements—as is appropriate—that they were consultants to corporations that produce RFD equipment, the authors failed to disclose that 4 of 5 are on the editorial board of RAPM and all 5 are current officers in the medical organization that owns RAPM : that is, the American Society of Regional Anesthesia and Pain Medicine. Noteworthy, there was no published response from the MINT trial investigators to the Daring Discourse criticisms, either in the aforementioned example or in downstream venues where some of the same Daring Discourse authors continued their widely disseminated criticisms of the JAMA /MINT trials report. We believe that these actions taken by the Daring Discourse authors and RAPM have unfairly tipped the scales in the evaluation and application of RFD treatment of low back pain. In our commentary, we discuss: (1) the challenges associated with using clinical trials to predict clinical efficacy, (2) appropriate and inappropriate uses of postpublication commentary on original research findings, (3) the use of inappropriate commentary (and related means) to alter clinical practice in the presence of contradictory research findings, and (4) potential conflicts of interest related to the authors' and Journal's publication of the unopposed MINT trials criticism.